How difficult are the Financial Statements to read? - Sumiyati Sumiyati; Rulyanti Susi Wardhani; Hengky Veru Purbolakseto; Hendri Warno (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This paper examines the relationship between financial performance and Annual Readability Reporting. This study is interesting in that companies should submit reports concisely and are easy to read. However, it turns out that many company managers submit management reports in many sentences, especially when financial performance is not in good condition. An interesting finding of this paper is that net income has a significant negative effect on ARR, which indicates that even when management earns profits, the language of reporting submissions by management is quite difficult for users of financial statements to read. This study uses 66 years of observation of companies listed on the Indonesia Stock Exchange and tests the hypothesis using multiple linear regression and correlation. The results show that companies with high ARR with higher financial performance. Service companies in Indonesia need to convey their performance using more words, especially when financial conditions are not good. As measured by ROA, excellent financial performance significantly influences the readability of annual financial statements. The implications of this research are mainly for the service sector, there is a management behavior that has a habit of saying more words even though the profit is positive.